2022
DOI: 10.3389/fradi.2022.981501
|View full text |Cite
|
Sign up to set email alerts
|

The changing landscape of cerebral revascularization surgery: A United Kingdom experience

Abstract: ObjectiveWe describe the chronological trends in cerebral revascularization surgery through a single-surgeon experience; and we review whether in the context of giant and fusiform cerebral aneurysms, flow-diverting stents have impacted on the use of cerebral revascularization surgery.MethodsWe review our single institution prospectively collected database of cerebral revascularization procedures between 2006 and 2018. Comparing this to our database of flow-diverting endovascular stent procedures, we compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Starauss et al demonstrated not only the use of cerebral revascularization declined after introduction of flow diverting stents but also the patients selected for cerebral revascularization had poorer pre operative modified Rankin score Same was reported by Lawton that cerebral revascularization case reduced for aneurysm after FDA approved flow diverter stent. [12]…”
Section: Reasons For Decline In Revascularization Proceduresmentioning
confidence: 99%
“…Starauss et al demonstrated not only the use of cerebral revascularization declined after introduction of flow diverting stents but also the patients selected for cerebral revascularization had poorer pre operative modified Rankin score Same was reported by Lawton that cerebral revascularization case reduced for aneurysm after FDA approved flow diverter stent. [12]…”
Section: Reasons For Decline In Revascularization Proceduresmentioning
confidence: 99%